Suku baduy sebagai simbol hidup harmonis dan praktik ekologi berkelanjutan - Rahmatul ula, aristya luna (Maliki Interdisciplinary Journal, 2025)
The uniqueness of the Baduy tribe with the application of ecological practices that strongly uphold nature preservation is a harmonious example in maintaining Indonesia’s natural wealth. They implement a system developed on the basis of the need to respect, preserve, and continue life in accordance with the circumstances, conditions, abilities, and values of the community concerned. Therefore, this article aims to find out how the Baduy Tribe’s living practices can reflect the principles of sustainable ecology and the extent to which the Baduy Tribe’s way of life can be used as a model for other communities in an effort to realize a harmonious and sustainable life. This study uses a descriptive qualitative method to describe the lifestyle and ecological practices applied by the Baduy tribe, so that the results of the discussion show that the Baduy tribe not only maintains their food security through sustainable farming practices, but also acts as a symbol of life in harmony with nature.